1988
DOI: 10.1177/019459988809800205
|View full text |Cite
|
Sign up to set email alerts
|

An Objective Assessment of Voice Production after Radiation Therapy for Stage I Squamous Cell Carcinoma of the Glottis

Abstract: Radiation therapy has been the primary treatment for early glottic carcinoma, especially when restoration of normal voice is essential; yet objective evidence of the status of vocal function after treatment is lacking. The purpose of this study was to assess vocal characteristics of patients with glottic carcinoma after they had undergone radiation therapy. Twenty males, who had previously been treated with external beam irradiation for T1N0M0 squamous cell carcinoma with no subsequent evidence of recurrence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
52
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 15 publications
8
52
0
Order By: Relevance
“…This finding may support the previously postulated notion that radiotherapy for early glottic cancer causes fibrosis in vocal fold tissue. 16 Decorin was found to be preserved, more or less, in all cases with type I postcordectomy scar, while it varied after deeper cordectomy procedures. Decorin is a small chain proteoglycan, which is normally distributed in the superficial layer of the lamina propria of human vocal folds.…”
Section: Discussionmentioning
confidence: 88%
“…This finding may support the previously postulated notion that radiotherapy for early glottic cancer causes fibrosis in vocal fold tissue. 16 Decorin was found to be preserved, more or less, in all cases with type I postcordectomy scar, while it varied after deeper cordectomy procedures. Decorin is a small chain proteoglycan, which is normally distributed in the superficial layer of the lamina propria of human vocal folds.…”
Section: Discussionmentioning
confidence: 88%
“…Other authors have also demonstrated poor voice quality after endoscopic laser treatment, 34,35 whereas Lehman et al 36 and Schuller et al 37 reported that their patients subjectively assessed their voices as near normal after radiotherapy. The finding of better voice quality after radiotherapy compared with endoscopic laser treatment has been confirmed by other authors.…”
Section: Discussionmentioning
confidence: 98%
“…Voice impairment in patients after treatment for early glottic cancer has been reported in several studies, ranging from 14 to 92% of the patients [1,6,9,16,24,25]. Furthermore, several studies on the inXuence of voice problems on quality of life revealed that in 27 up to 58% of the patients experienced diYculties in communication abilities leading to a disrupted social life [3,8,12,17,[19][20][21][22]25].…”
Section: Introductionmentioning
confidence: 99%